MAPPING AND ANALYSIS THE OPERATIONAL MANAGEMENT OF DIGITAL MULTIMEDIA PRODUCTS AT PT DIRECT VISION - Daryono Daryono (Performance: Jurnal Personalia, Financial, Operasional, Marketing dan Sistem Informasi, 2013)
Carrying the “Astro” brand, PT Direct Vision (“PT DV”) provides subscription-based television access for homes and commercial establishments. PT DV transmits up-to-the-minute information and the latest in local and international entertainment to its satellite in orbit, which returns the signal to the Southeast Asia region. The transmission can only be translated into audio video using a digital multimedia system (“DMS”) made up of an outdoor mini-satellite dish, a decoder, and a smart card. DMS products are manufactured abroad and imported to be distributed to new subscribers. The purpose of this Final Project is to evaluate the current distribution system of DMS products and suggest alternatives to promote cost efficiency in the logistical operations. Overall cost of distribution was considered relatively high and opportunities to lower cost can be attributed to better planning and key performance indicators. The process reference model was used as an approach to evaluate the current distribution system and to present alternatives for improvement. Of the proposed alternatives, major points for improvement include utilizing regional distribution centers, appointing a third party logistics service provider, optimizing economic order quantity, and establishing key performance indicators.